Justice Brennan : Liberal Champion - Stern, Seth (Seth Ross), 1975- (Book collections on Project MUSE., 2013)
"[This book] is a sweeping and revealing insider look at court history and the life of William Brennan, champion of free speech and public access to information, and widely considered the most influential Supreme Court justice of the twentieth century."--Jacket